Combined targeting of pathways regulating synaptic formation and autophagy attenuates Alzheimer's disease pathology in mice - Christiana Bjorkli; Christiana Bjorkli; Mary Hemler; Mary Hemler; Joshua B. Julian; Axel Sandvig; Axel Sandvig; Axel Sandvig; Axel Sandvig; Ioanna Sandvig; Ioanna Sandvig (Frontiers Media S.A., 2022)
All drug trials completed to date have fallen short of meeting the clinical endpoint of significantly slowing cognitive decline in Alzheimer's disease (AD) patients. In this study, we repurposed two FDA-approved drugs, Fasudil and Lonafarnib, targeting synaptic formation (i.e., Wnt signaling) and cellular clearance (i.e., autophagic) pathways respectively, to test their therapeutic potential for attenuating AD-related pathology. We characterized our 3xTg AD mouse colony to select timepoints for separate and combinatorial treatment of both drugs while collecting cerebrospinal fluid (CSF) using an optimized microdialysis method. We found that treatment with Fasudil reduced Aβ at early and later stages of AD, whereas administration of Lonafarnib had no effect on Aβ, but did reduce tau, at early stages of the disease. Induction of autophagy led to increased size of amyloid plaques when administered at late phases of the disease. We show that combinatorial treatment with both drugs was effective at reducing intraneuronal Aβ and led to improved cognitive performance in mice. These findings lend support to regulating Wnt and autophagic pathways in order to attenuate AD-related pathology.